Acceptance of traditions and transformation of style in art education in the period of globalization (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article analyzes the art education systems of different countries, teaching methods, the role of the pedagogical system and the teacher himself in the formation of the student and the education of his own artistic style in modern conditions of globalization and its influence on preservation. Identity Globalization is an inevitable phenomenon that has already arrived, in the process of which goods, information, knowledge and cultural values are exchanged around the world, and it is becoming more and more interconnected.Globalization processes in culture and art have a negative impact on art education and are reflected in qualitative changes in teaching methods and techniques, affect the preservation of identity, cultural heritage, mentality and established traditions in the training of specialists. The market makes inorganic demands on the artist, which greatly distort his unique vision of the world. Reality often requires a lot from a modern artist that is not related to creativity. At some point, the market begins to require him to be a manager, a bureaucrat, to be able to build a system of promotion and growth using fashionable trends. As a result of transformations in the course of globalization, education has lost its true purpose - the development of elevated creative foundations of the individual, the formation of a person as a spiritual being, enlightenment and the desire for improvement [5].Our task in the conditions of inevitable globalization is to choose for ourselves and to form and preserve our system of art education, taking into account all the risks of the Bologna process with its motto at the head: "nothing personal, only business." Creativity does not tolerate universality, creativity has no limits and cannot be subject to uniform standards. Artistic creativity as a form of self-expression is an important part of the development of a modern person's personality, as a form of survival in a global world.The globalization of education is characterized by the expansion of the interests of developed countries into the corresponding areas of developing countries. It is obvious that globalization processes are beneficial mainly to countries with developed economies, which are trying to strengthen their dominant position in all possible spheres, science, education, sociology [14]. Less developed countries are seeing an outflow of young people in search of a better life.Thus, the problem to be solved is the preservation of traditional art education with a master teacher at the head of this process in the face of inevitable changes in the globalization of society and the education system.
Keywords: identity; traditions; globalization; art education; creativity; teaching method; pedagogical system; artist; individuality